VoIP security - Ransome, James F.; Rittinghouse, John W. (Amsterdam ; Boston : Elsevier, 2005)
Voice Over Internet Protocol Security has been designed to help the reader fully understand, prepare for and mediate current security and QoS risks in todays complex and ever changing converged network environment and it will help you secure your VoIP network whether you are at the planning, implementation, or post-implementation phase of your VoIP infrastructure. * This book will teach you how to plan for and implement VoIP security solutions in converged network infrastructures. Whether you have picked up this book out of curiosity or professional interest ... it is not too late to read this book and gain a deep understanding of what needs to be done in a VoIP implementation. * In the rush to be first to market or to implement the latest and greatest technology, many current implementations of VoIP infrastructures, both large and small, have been implemented with minimal thought to QoS and almost no thought to security and interoperability.
The (business) value of VoIP -- Digital voice fundamentals -- Telephony 101 -- Packet technologies -- VoIP processing -- VoIP implementation basics -- VoIP security risks -- VoIP security best practices -- VoIP security and the law -- The future of VoIP.
Includes bibliographical references (p. 379-384) and index.
Keywords: Internet telephony -- Security measures; Electronic books